Hospitality and Welcome as Christian Imperatives in Relation to 'the Other' - Constantineanu, Corneliu (Transformation, 2018)
Many would acknowledge today that the question of understanding and relating to 'the other' has become a vital and urgent question in our globalised world, which brings 'the other' right in front of us. The tragic realities of migration around the world and the recent refugee crisis point forcefully to the scale and urgency of the matter. This article offers a biblical perspective on the unambiguous love and concern of God for strangers, immigrants and refugees, with the resulting imperative for Christians to practice hospitality and welcome 'the other'. It is argued that hospitality and welcome represent the very heart of the mission of God and the essence of the gospel illustrated in the self-giving of God in Christ and in the Spirit, and so they should become a central concern for all those who follow Christ in our suffering and troubled world.